Pengaruh Pendidikan, Gaya Kepemimpinan, dan Disiplin Kerja Terhadap Kinerja Karyawan (Studi Karyawan SMK Negeri 1 Kepanjen) - Fitri, Elysia; Salim, Muhammad Agus; Novianto, Abdullah Syakur (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the influence of education, leadership style, and work discipline on employee performance at SMK Negeri 1 Kepanjen. This study uses a quantitative method with a population of employees at SMK Negeri 1 Kepanjen and involves 40 respondents selected through saturated sampling techniques. Data were obtained from primary sources through questionnaires and analyzed using SPSS version 25.0. The test results show that both simultaneously and partially, the variables Education (X1), Leadership Style (X2), and Work Discipline (X3) have a positive effect on Employee Performance (Y). Keywords: Educaton, Leadership Style, Work Dicipline, Employee Performance.